Peran Religius Culture dalam Pembentukan Karakter Religius pada Siswa di MTS Ma’arif Garung Wonosobo - Susan Asasiyah; Sri Haryanto; Darul Muntah (IHSANIKA : Jurnal Pendidikan Agama Islam, 2025)
Religious culture is a school-based value system that aims to shape students' religious character through habituation, modeling, and a conducive spiritual environment. This research aims to describe the implementation and effectiveness of religious culture at MTs Ma’arif Garung Wonosobo in building students' religious character. The method used is qualitative with data collection techniques through observation, interviews, and documentation. The findings show that religious culture is implemented through daily, weekly, and periodic religious activities. The presence of teachers as role models, social support among students, and a religious atmosphere in the school environment are the main supporting factors. Meanwhile, obstacles come from some students’ lack of discipline, different religious backgrounds, and limited infrastructure. The implication of this research highlights the importance of consistency and collaboration between all school elements to internalize religious values in students' daily lives.